Comparison of empathy levels of dentistry students after two teaching strategies of administering local anesthesia - Teng, Celian N.; Erlyn A. Sana, PhD (Manila National Teacher Training Center for the Health Professions, 2020)
Introduction: To this date, the student-to-student (STS) model of injection serves as the default teaching strategy for dentistry students to develop skills in Local Anesthesiology. This study tested if the use of such strategy, as well as injecting friends and members of their families can also be instrumental in helping second year dental proper students acquire or increase their level of empathy. Students also explained how they view their experience of injecting local anesthesia on their peers and others. Methods: This study used the quasi-experimental research design. Levels of empathy of second year dental students from a private tertiary institution were determined before and after any injection activities were performed using the Jefferson Scale of Empathy-Health Professions Students (JSE-HPS) version. The JSE-HPS is a validated scale used in different health care settings (Sherman, 2005) with scores ranging from 20 to 140 points. One group administered the injections using the STS model of injection and another group performed the injections using their friends and family members. Pre-test and post-test scores of both groups were collected. Mean, frequency and percentage distributions, and t-test for both paired and unpaired groups were used to analyze data. Conveniently selected second-year dentistry students from both groups participated in a focus group discussion. Qualitative data were analyzed using content analysis and were corroborated with the quantitative results. xiv Results: Data showed that the pre-test level of empathy of second-year dental students ranged from 82 to 132 with a mean score of 107.46 (SD=10). Their post-test empathy level ranged from 82 to 134 with mean equal to 112.46 and SD=12.45. T-test yielded -3.76 at p=0.00 providing evidence that the two strategies improved the empathy level of students. Results also showed no significant change for the STS group. FGD results showed that students appreciated the importance of empathy both when they experienced being patients themselves but also when they injected the members of their family as well as their friends. Conclusion: Both the quantitative and qualitative results affirm that while the overall level of empathy increased after the two strategies, those who injected the local anesthesia to actual patients like members of their family and friends outside the class registered the significant increase compared to the STS.
Thesis (Master in Health Professions Education)
Panel Members: Erlyn A. Sana, PhD, Chair/Adviser. Melflor A. Atienza, MD MHPEd, Reader/Critic. Members: Maria Lourdes Dorothy S. Salvacion, DDM, MHPEd, Nemuel S. Fajutagana, MD, MHPEd, Maria Geraldine S. Chanco, DMD, MHPEd
Keywords: Student-to-student model of injection; Empathy; Local anesthesia in dentistry